Analisis Algoritma Rabin-Karp Pada Kamus Umum Berbasis Android - Herriyance Herriyance; Handrizal Handrizal; Siti Dara Fadilla (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2017)
Development of the era had a considerable impact on the existence of a language. To overcome this there are some efforts to be made, one of which is to create a dictionary, a dictionary that was made to be practical and quick in use. Dictionary in question is a dictionary based on Android. To create a dictionary-based android can use string matching algorithm, one of the string matching algorithm is the Rabin-Karp algorithm, Rabin-Karp algorithm perform string matching hash value based on the text and the pattern hash value. The study produced an android based dictionary application which the base number is used to generate a hash value greatly affects the speed of search words. Average running time of 10 attempts to search for words is 14.9 ms.